Pengaruh Motivasi Guru Mata Pelajaran Al-Qur’an Hadits Terhadap Prestasi Siswa Ma Sirojul Falah - Shenta Mandela; Edy Edy (STIT Sirojul Falah Bogor, 2022)
Education and teaching is a goal-conscious process. One of the teaching objectives is achieved or not, it can be seen from the learning outcomes achieved by students. One of the factors that influence student achievement is motivation. This study aims to determine the effect of teacher motivation on the subject of Al-Qur'an Hadith on student achievement at MA Sirojul Falah. This research is a quantitative research using the statistical technique of Product Moment correlation. The results showed that based on research on variables X and Y regarding the influence of the motivation of the Al-Qur'an Hadith subject teacher on student achievement at MA Sirojul Falah, it showed that the value of the calculation of r product moment was 0.12. Based on the interpretation table, the value of the order is between 0.00-0199, so it can be concluded that the correlation between the influence of the motivation of the Al-Qur'an Hadith teacher on the student achievement of MA Sirojul Falah is categorized as very low. Keywords: : student motivation, achievement, MA Sirojul Falah